2000
DOI: 10.1038/sj.onc.1203474
|View full text |Cite
|
Sign up to set email alerts
|

Similar but distinct effects of the tristetraprolin/TIS11 immediate-early proteins on cell survival

Abstract: The immediate early protein tristetraprolin (TTP) is required to prevent inappropriate production of the cytokine TNF-a, and is a member of a zinc ®nger protein family that is associated with RNA binding. TTP expression is induced by TNF-a, and evidence indicates that TTP can bind and destabilize the TNF-a mRNA. TTP and the closely related TIS11b and TIS11d proteins are evolutionarily conserved, however, and induced transiently in various cell types by numerous diverse stimuli, suggesting that they have additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
76
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 55 publications
(72 reference statements)
11
76
0
Order By: Relevance
“…Like some other immediate early proteins, in certain contexts TTP is also expressed during induction of apoptosis (27)(28)(29)(30). Consistent with the model that TTP/TIS11 proteins influence growth, survival, or apoptotic signals, we have determined that their constitutive expression at modest levels induces apoptosis through the mitochondrial pathway (31). We have also shown that TTP has diverged functionally from the other two TTP/TIS11 proteins, in that TTP alone dramatically sensitizes cells to the apoptotic stimulus of TNF␣ (31,32).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Like some other immediate early proteins, in certain contexts TTP is also expressed during induction of apoptosis (27)(28)(29)(30). Consistent with the model that TTP/TIS11 proteins influence growth, survival, or apoptotic signals, we have determined that their constitutive expression at modest levels induces apoptosis through the mitochondrial pathway (31). We have also shown that TTP has diverged functionally from the other two TTP/TIS11 proteins, in that TTP alone dramatically sensitizes cells to the apoptotic stimulus of TNF␣ (31,32).…”
supporting
confidence: 50%
“…Consistent with the model that TTP/TIS11 proteins influence growth, survival, or apoptotic signals, we have determined that their constitutive expression at modest levels induces apoptosis through the mitochondrial pathway (31). We have also shown that TTP has diverged functionally from the other two TTP/TIS11 proteins, in that TTP alone dramatically sensitizes cells to the apoptotic stimulus of TNF␣ (31,32). This last finding suggests that TTP could contribute to the cellular decision between activation or apoptosis in response to TNF␣.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Since a series of regulators relevant for oncogenic growth including cyclins, growth factors and proto-oncogenes contain AREs with an UUAUUUAUU motif (Chen and Shyu, 1995), it is conceivable that TTP in fact has a broader spectrum of target mRNAs in the tumor cells. Such targets may also include antiapoptotic genes, as continuous expression of TTP was observed to induce apoptosis in various cell lines (Johnson et al, 2000). Although we formally cannot exclude the possibility of .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several publications demonstrate that TTP family proteins are phosphorylated 9 and are possible targets along the p38 MAPK pathway. 10,11 At the biological level, TTP family members have been described as involved in cell differentiation and apoptosis, 12,13 in the regulation of the cell response to growth factors and in the development of cancer. In particular, it has been demonstrated that TTP proteins target and destabilize mRNAs encoding growth factors' signaling transducers, particularly downstream of EGF 14 and IGF-I receptors.…”
Section: Introductionmentioning
confidence: 99%